Optimalisasi Kegiatan Fire Drill bagi Karyawan dalam Menjaga Keselamatan Kerja di Gedung Kantor PT MGA - Kosim, Muhamad Engkos; Suryatman, Tina Hernawati; Siskayanti, Rini (Program Studi Teknik Industri Universitas Muhammadiyah Tangerang, 2025)
Fire drill training in the workplace is very important to familiarize employees in the event of a fire. This study examines simulation training in dealing with fire emergencies in the PT MGA office building located in South Jakarta with 23 participants. With proper evacuation simulation training during a fire emergency, it is expected to minimize losses that can occur. Evaluation of the implementation of fire drills is needed to determine how the implementation of fire drills improves the safety of PT MGA employees and how employees understand the implementation of fire drills. In this study, the author used a qualitative descriptive approach and primary and secondary data sources. The results of this study show that the implementation of fire drills is quite effective, with the majority of employees understanding evacuation procedures However, several technical constraints and improvements to facilities and infrastructure such as the type of fire extinguisher, automatic sprinkler system, alarm and hydrant need to be followed up. Follow-up and further training are recommended to improve preparedness.Keywords: Fire Drill, Fire, Evacuation, Office Building, Fire Extinguisher